2016
DOI: 10.3928/01484834-20151214-08
|View full text |Cite
|
Sign up to set email alerts
|

Virtual TeamSTEPPS ® Simulations Produce Teamwork Attitude Changes Among Health Professions Students

Abstract: These findings indicate the potential impact that virtual learning experiences may have on teamwork attitudes in learners across professions on multiple campuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Regarding sample size, the average number of participants was 39.69 (min = 10, max = 148, SD= 37.33). Looking more closely at their study design, 17 studies used an experimental design (pre-test/post-test, group comparisons or control/test group comparisons) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) , nine were observational studies (18)(19)(20)(45)(46)(47)(48)(49)(50) , and one was based on qualitative interviews (51) .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Regarding sample size, the average number of participants was 39.69 (min = 10, max = 148, SD= 37.33). Looking more closely at their study design, 17 studies used an experimental design (pre-test/post-test, group comparisons or control/test group comparisons) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) , nine were observational studies (18)(19)(20)(45)(46)(47)(48)(49)(50) , and one was based on qualitative interviews (51) .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This model has become the standard of comparison for other models . All 19 reviewed studies consistently reported significant improvement in attitudes related to communication, leadership, teamwork skills, and mutual support following the implementation of TeamSTEPPS . A variety of evaluation tools related to TeamSTEPPS were also discussed in the reviewed literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most common evaluation tools discussed were the TeamSTEPPS Teamwork Attitude Questionnaire and Teamwork Perception Questionnaire. Both of these tools were shown to be valid, reliable, and effective in determining readiness for TeamSTEPPS implementation as well as postimplementation success …”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations